Pemanfaatan tanin dari kulit kayu tingi (Ceriops tagal) sebagai bahan penyamak nabati: pengaruh penambahan alum dan mimosa - Emiliana Kasmudjiastuti; Sri Sutyasmi; Titik Purwati Widowati (Majalah Kulit, Karet, dan Plastik, 2015)
This research aimed at determining the effectiveness of the Tingi bark’s extract as vegetable tanning material and the optimum formulations of Tingi extract for lining leather tanning, when combined with alum and mimosa. The research variables included the solution compositions of alum, Tingi extract, and mimosa, as well as the process sequences in which the hides were exposed to each aforementioned solution. There were 8 (eight) different treatments performed in this research; those are alum (4%)-Tingi, alum (6%)-Tingi, alum (4%)-Tingi-mimosa (5%), alum (6%)-Tingi-mimosa (5%), Tingi-alum (4%),Tingi-alum (6%), Tingi-mimosa (5%)-alum (4%), and Tingi-mimosa (5%)-alum (6%). Characterization methods included chemical and physical tests. The results show that the Tingi extract can be used as vegetable tanning material, and the optimum properties were obtained when the alum (4%) was added after the Tingi extract {Tingi-alum (4%)}.The optimum properties were shrinkage temperature of 86 oC; total ash content of 0.73%; water soluble matter of 0.89%; pH of 3.78; degree of tannage of 96.37%; tensile strength of 370.65 kg/cm2; elongation at break of 36.52%; rubfastness of 5 (dry); and 4 (wet). The resulting leather also meet the requirements of Ethiopian Standard 1185:2005, Leather-Lining leather-Specification. Keywords: Tingi bark’s extract, alum, mimosa, vegetable tanning, lining leather.ABSTRAKPenelitian ini bertujuan untuk mengetahui efektifitas ekstrak kulit kayu Tingi sebagai bahan penyamak nabati dan formulasi ekstrak Tingi yang optimal pada penyamakan kulit lapis, ketika dikombinasikan dengan alum dan mimosa. Variabel penelitian meliputi komposisi larutan alum, ekstrak Tingi, dan mimosa, serta urutan proses di mana kulit diekspos ke masing-masing larutan tersebut di atas. Terdapat 8 (delapan) perlakuan berbeda dalam  penelitian ini, yaitu alum (4%)-Tingi, alum (6%)-Tingi, alum (4%)-Tingi-mimosa (5%), alum (6%)-Tingi-mimosa(5%), Tingi-alum (4%), Tingi-alum (6%), Tingi-mimosa (5%)-alum (4%), and Tingi-mimosa-alum (6%). Metode karakterisasi meliputi pengujian kimia dan fisika. Hasil penelitian menunjukkan bahwa ekstrak Tingi dapat digunakan sebagai bahan penyamak nabati, dan sifat-sifat optimum diperoleh ketika penambahan alum (4%) dilakukan setelah penambahan ekstrak Tingi {Tingi-alum (4%)}. Sifat-sifat optimum tersebut adalah: suhu kerut 86oC; kadar abu jumlah 0,73%; kadar zat larut dalam air 0,89%; pH 3,78; derajat penyamakan 96,37%; penyamakan masak; kekuatan tarik 370,65 kg/cm2; kemuluran 36,52 %; ketahanan gosok cat nilai 5 (kering) dan 4 (basah). Kulit yang dihasilkan juga memenuhi persyaratan Ethiopian Standard 1185: 2005, Leather–Lining leather-Specification.  Kata kunci : kulit kayu Tingi,  alum, mimosa, bahan penyamak nabati,  kulit lapis.